Nyikap Diri Ngiga Pengawa Training Project (Community Service Program), Saratok anjuran MSc.HRD Kohort Februari 2017 - Helmi, Sumilan; Victoria, Jonathan (Universiti Malaysia Sarawak (UNIMAS), 2017)
Saratok, Sarawak: 11 Mei 2018